Clinicopathological analysis of patients diagnosed with DRESS - Burçin Cansu Bozca; Anıl Alpsoy; Asli Bilgiç; Cumhur İbrahim Başsorgun; Betül Ünal; Erkan Alpsoy (Galenos Publishing House, 2023)
Background and Design: Drug reaction with eosinophilia and systemic symptoms (DRESS) is an uncommon, but potentially fatal, adverse drug reaction. Despite the alarming statistics regarding morbidity, mortality, and hospitalizations, epidemiological data on DRESS are insufficient. In this investigation, we sought to determine the etiology, clinicopathological characteristics, and prognosis of DRESS cases at our institution. Materials and Methods: In this retrospective, single-center study, 23 patients with DRESS examined between January 2014 and September 2020 were included according to the European Registry of Severe Cutaneous Adverse Reactions (RegiSCAR) scoring system. Patients were examined between January 2014 and September 2020. Descriptive statistics, Shapiro-Wilk test, Kolmogorov-Smirnov test, Mann-Whitney U test, Pearson chi-square test, and Fisher's exact test were performed. Results: The most frequently detected culprit drug category was anticonvulsants. Maculopapular eruption (100%) and elevated liver function tests (82%) were the most prevalent cutaneous and laboratory findings, respectively. Patients with elevated liver enzymes were more likely to exhibit facial erythema/edema and lymph node enlargement than those without (p=0.021 and p=0.103, respectively). The predominant pathological features were sparse vacuolization of the dermal-epidermal junction and superficial perivascular lymphohistiocytic inflammation with eosinophils. Two patients died during the period of follow-up, three patients were lost to follow-up, and eighteen patients recovered completely. Conclusion: Our research demonstrated that facial erythema/edema and lymph node enlargement are more prevalent in patients with elevated liver enzymes. Cyclosporine may be a treatment option in the fragile age group to prevent systemic corticosteroid complications. Early diagnosis and treatment that balances benefits and risks remain the most important determinants of prognosis